Shifting song frequencies in response to anthropogenic noise: a meta-analysis on birds and anurans. (12th April 2016) - Roca, Irene T.; Desrochers, Louis; Giacomazzo, Matteo; Bertolo, Andrea; Bolduc, Patricia; Deschesnes, Raphaël; Martin, Charles A.; Rainville, Vincent; Rheault, Guillaume; Proulx, Raphaël
Lay Summary: One strategy that vocally active animals may use to attenuate the effect of acoustic masking by anthropogenic noise is to shift the emitted signal toward higher frequencies. Bird species increase their dominant frequencies when confronted with anthropogenic noise. Yet, anuran species seem less prone to such shifts. Birds' frequency shift is broader when the frequency component of the song is within the noise range, and the bird species size is small. Abstract : Anthropogenic noise has been shown to alter the transmission environment and distort acoustic signals, prompting vocalizing species to use compensatory mechanisms. Through a meta-analysis we investigated the relative importance of biological and contextual factors predisposing species to shift their singing/calling frequencies in response to anthropogenic noise. We gathered data from 36 studies, synthesizing information on more than 160 experiments and 60 bird and anuran species. To estimate the breadth of frequency shift, we calculated a standardized effect size using Hedges' g . We fitted a multilevel linear mixed-effect model on g as the dependent variable weighted by its inverse variance, with typical frequency, body mass, experimental condition, and noise source type as independent terms. Our results reveal broader shifts in smaller bird species when compared with bigger species, an effect that was emphasized in the low-frequency component of the song spectrum. Birds increased their dominant frequencies when confronted to anthropogenic noise, whereas anurans were less prone to such shifts. Human-altered acoustic environments can be considered a novel selective force impelling change to the communication patterns of many vocalizing species.